Studies on Hysteria ( Vol.3 ) - Breuer, Josef and Freud, Sigmund; Translated by James and Alix Strachey ; Edited By James and Alix Strachey, Assisted By Angela Richards ; The Present Volume Edited By Angela Richards (England Penguin Books, 1995)
Psychoanalysis is bedded in the work on hysteria done by Freud and Breuer, and this volume contain both their 'Preliminary Communication' of 1893 and the fuller publicatios of 1895, with its famous cade histories.
Include Index,Bibliography and Abbrivations.
Keywords: Hysteria -- Psychoanalysis